Affects of Working Capital Management on Firm's Performance: Evidence from Turkey - Gamze Vural; Ahmet GÃ¶khan SÃ¶kmen; Emin Hüseyin Çetenak (International Journal of Economics and Financial Issues, 2012)
The working capital management has an important role for the firm’s success or failure because of it’s’ effect on firm’s performance and liquidity. The study is based on secondary data collected from 75 manufacturing firms listed on Istanbul Stock Exchange Market for the period 2002-2009 with an attempt to investigate the relationship between working capital management components and performance of the firms by using dynamic panel data analysis. The results demonstrate that firms can increase profitability measured by gross operating profit by shortening collection period of accounts receivable and cash conversion cycle. Leverage as a control variable has a significant negative relationship with firm value and profitability of firms. This means, increase in the level of leverage will lead to decline in the profitability of the firm and the value of the firm.